Evaluation of three-way cross ‘jharsim’ variety of chicken under different system of management - KUMAR, NIRAJ; PRASAD, SUSHIL; KUMAR, RAVINDRA (The Indian Journal of Animal Sciences, 2021)
The present research work was conducted on 600 day old Jharsim chicks to evaluate the performance of Jharsim poultry under different system of management. The average value of day old Jharsim birds was 31.27 g. Significant effect of body weight and body weight gain at various stages of growth was observed under different condition of management. The overall average body weight in deep litter system of management was 1547.55±8.69 g at 20 weeks of age. The corresponding values for semi-intensive and backyard system were 1462.95±3.86 and 1207±10.42 g respectively. The average monthly body weight gain under deep litter system was 605.60±7.25 at 16th- 20th weeks of age. The corresponding values for semi-intensive and backyard system of management were 406.6±5.80 g and 280±4.67 g respectively. Feed consumption was observed to be significantly higher in deep litter system than semiintensive system of management. Significant effect of different carcass traits was observed under different systems of management.